Rasputin swims the Potomac : a novel - Fountain, Ben (Flatiron Books, 2026)
Reporter Clarence Thomas Jr. is looking for a great story, former country music teen star Faith Spack has parlayed her fame into a job at the White House, and the two-term incumbent president is campaigning for a constitutionally dubious third term. After an outbreak at a campaign rally, a mysterious new pandemic of "weeping sickness" sweeps the nation, threatening the president's hold on the Oval Office. Desperate to retain power, he enlists the mystical pro wrestler Rasputin to help ensure his reelection and guarantee additional seasons of his presidential reality TV show, The Real West Wing. But as Rasputin's appeal threatens to exceed the president's, and the wrestler's supposedly supernatural powers start to seem like the real thing, the campaign finds itself trapped in a spandex-clad destiny no number of executive orders can control, one in which both Clarence and Faith are compelled to play increasingly large parts. Hilarious, compelling, and tragically relevant, Rasputin Swims the Potomac is both an escape and a warning, a scathing satire that explores the twists and turns of American democracy as it hurtles toward authoritarianism.